2016
DOI: 10.2169/internalmedicine.55.5156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Autoantibodies and the Efficacy of Immunotherapy for Autoimmune Cerebellar Ataxia

Abstract: Objective Autoimmune cerebellar ataxias were recently reported to be treatable. However, the proportion of patients with cortical cerebellar atrophy of unknown etiology with autoimmune-associated cerebellar ataxia and the actual effectiveness of immunotherapy in these diseases remain unknown. Methods We measured the level of autoantibodies (including anti-gliadin antibody, anti-glutamic acid decarboxylase (GAD) antibody, and anti-thyroid antibody) in 58 Japanese patients with cerebellar ataxia, excluding those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…More recently, the prevalence of GA in Asian countries has been found to be higher than was previously estimated. 22,23 For example, patients with GA have recently been reported in Japan. 23 A survey in China also showed that the prevalence rates of positive-anti-transglutaminase 6 (TG6) IgA were 35% in 100 sporadic CA patients and 9.8% in 51 healthy controls (p = 0.001).…”
Section: General Issues On Diagnosis and Immunotherapies Prevalencementioning
confidence: 99%
“…More recently, the prevalence of GA in Asian countries has been found to be higher than was previously estimated. 22,23 For example, patients with GA have recently been reported in Japan. 23 A survey in China also showed that the prevalence rates of positive-anti-transglutaminase 6 (TG6) IgA were 35% in 100 sporadic CA patients and 9.8% in 51 healthy controls (p = 0.001).…”
Section: General Issues On Diagnosis and Immunotherapies Prevalencementioning
confidence: 99%
“…Hashimoto's encephalopathy may present with elevated protein levels in the CSF and slow waves on EEG; however, cerebellar-type is unlikely to show such abnormalities (7). Hashimoto's encephalopathy is the most prevalent cause of autoimmune ataxia without tumors (51%) and is unlikely to include nystagmus, as observed in anti-GAD antibody-positive cerebellar ataxia or gluten ataxia (8). Cerebellar syndrome is a major type of PNS, but our patient had no antibodies for PNS; furthermore, ataxia caused by PNS does not typically disappear with the use of steroids alone.…”
Section: Discussionmentioning
confidence: 64%
“…Neuroimaging studies are nonrevealing; however, increased level of protein in the CSF has usually been found in these cases. The nature of the autoantibodies involved in the pathogenesis of autoimmune thyroid disease and the mechanisms that cross anti-thyroid autoimmunity and encephalopathy are still undefined [7,8]. In most of the cases, the diagnosis was based on neurological symptoms, negative CSF evidence of viral or bacterial infection and presence of anti-thyroid antibodies.…”
Section: Discussionmentioning
confidence: 99%